The influence of personal and role factors in the formation of customer orientation behaviour towards the performance of financial planners in Malaysia - Chung, Muh Sha (2019)
Customer orientation behaviour which refers to the marketing concept demonstrated by salespersons to assist customers in making purchasing decisions has been the subject of sustained interest for the past decades. Despite numerous studies undertaken on salesperson customer orientation behaviour, a complete understanding of its antecedents and consequences are presently lacking especially in the professional sector. In the financial planning industry in particular, to serve customers better, financial planners ought to understand the customers‟ needs and wants. Financial planners are encouraged to prioritize customers‟ best interests by adopting customer orientation behaviour when providing financial planning services. Due to limited knowledge in this area, it is important to investigate the antecedents and consequences of customer orientation behaviour of financial planners in the financial planning industry. The antecedents discussed in the present study consist of personal factors (self-efficacy and employee engagement) and role factors (role ambiguity and role conflict). Besides, the consequences of customer orientation behaviour on financial planners‟ job performance was also being examined. The selected participants were licensed financial planners attached to financial planning firms in Malaysia. Structured self-administered questionnaires were distributed to 645 licensed financial planners. The collected data were then analysed by using SPSS version 25. Based on the results, four out of five hypothesized relationships were supported. Selfefficacy and employee engagement were found to be positively related to customer orientation behaviour. Role conflict was negatively related to customer orientation behaviour. Role ambiguity, however, was found to be unrelated to the adoption of customer orientation behaviour. Besides, customer orientation behaviour was found to have a significant impact on job performance. The findings will be useful in the development of financial planning in Malaysia